Business Success Review from Entrepreneur Orientation, Entrepreneur Competency, and Entrepreneur Leadership study on Small and Medium Enterprises (SMEs) in Mataram City - Santi Nururly; Mukmin Suryatni; Mahyudin Natsir; M. Ilhamudin (PT FORMOSA CENDEKIA GLOBAL, 2022)
Small and Medium Enterprises (SMEs) must have the capability and strategy to seize opportunities and renew the market. The business's success shows by being able to survive and be able to provide prosperity for entrepreneurs. This research examines business success in SMEs in Mataram City, which is associated with entrepreneurial orientation, entrepreneurial competence, and entrepreneurial leadership. The research sample takes from all SMEs in Mataram City, which has official permission from the government. Data collection was carried out by distributing questionnaires to SME leaders. The results show that entrepreneurial orientation, entrepreneurial competence, and entrepreneurial leadership can be aspects that can increase business success.